SESUDAH 50 TAHUN KITA HARUS BERANI MENGHADAP APA YANG TERJADI - Frans Magnis Suseno (Jurnal Ledalero, 2015)
The author gives a personal account of the 1965/1966 mass slaughter of so-called communists in central Java where he was living at the time, and more generally in Sumatra, Java and Bali. He continues with a detailed analysis. He then calls for fellow Indonesians to face up to the truth of the massacre, which until now has been erased from the collective historical memory of the nation. Kata-kata kunci: historical truth, Indonesian Communist Party, General Suharto, Accepting Responsibility, Reconciliation.